Elite athletes and pregnancy outcomes: A systematic review and meta-analysis - Wowdzia, J. B.; McHugh, T.-L.; Thornton, J.; Sivak, A.; Mottola, M. F.; Davenport, M. H. (Medicine & Science in Sports & Exercise, 2021)
Purpose: The purpose of this systematic review was to evaluate fetal and maternal pregnancy outcomes of elite athletes who had participated in competitive sport immediately before conception. Methods: Online databases were searched up to March 24, 2020. Studies of any design and language were eligible if they contained information on the relevant population (pregnant women), exposure (engaged in elite sport immediately before pregnancy), and outcomes (birth weight, low birth weight, macrosomia, preterm birth, fetal heart rate and pulse index, cesarean sections, instrumental deliveries, episiotomies, duration of labor, perineal tears, pregnancy-induced low back pain, pelvic girdle pain, urinary incontinence, miscarriages, prenatal weight gain, inadequate/excess prenatal weight gain, maternal depression or anxiety). Results: Eleven unique studies (n = 2256 women) were included. We identified "low" certainty evidence demonstrating lower rates of low back pain in elite athletes compared with active/sedentary controls (n = 248; odds ratio, 0.38; 95% confidence interval, 0.20-0.73; I2 = 0%) and "very low" certainty evidence indicating an increased odds of excessive prenatal weight gain in elite athletes versus active/sedentary controls (n = 1763; odds ratio, 2.47; 95% confidence interval, 1.26-4.85; I2 = 0%). Low certainty evidence from two studies (n = 7) indicated three episodes of fetal bradycardia after high-intensity exercise that resolved within 10 min of cessation of activity. No studies reported inadequate gestational weight gain or maternal depression or anxiety. There were no differences between elite athletes and controls for all other outcomes. Conclusions: There is "low" certainty of evidence that elite athletes have reduced odds of experiencing pregnancy-related low back pain and "very low"certainty of evidence that elite athletes have increased the odds of excessive weight gain compared with active/sedentary controls. More research is needed to provide strong evidence of how elite competitive sport before pregnancy affects maternal and fetal outcomes.